The Influence of Leadership and Motivation on Employee Performance of Document Control Division PT Mcdermott Indonesia Batam - Ibrahim, Ola; Nasruji (Yayasan Pendidikan Belajar Berdikari, 2025)
This study aims to analyze the effect of leadership and motivation on employee performance, with organizational culture as an intervening variable. This study was conducted on employees of the document control division at PT McDermott Indonesia Batam. The research method used is quantitative with multiple regression approach to test the relationship between variables. The results showed that leadership has a significant influence on employee performance with a significance value of 0.040 (<0.05). In contrast, motivation has no significant effect on employee performance with a significance value of 0.694 (> 0.05). Organizational culture is proven to have a significant influence on employee performance with a significance value of 0.004 (<0.05). The R Square test shows that leadership, motivation, and organizational culture together explain 41.5% of the variation in employee performance, while 58.5% is influenced by other factors outside of this research model. These findings indicate that effective leadership and strong organizational culture play an important role in improving employee performance. Therefore, companies need to strengthen leadership and build a positive organizational culture to create a productive and highly competitive work environment.